Avaliação de sintomatologia depressiva e déficit cognitivo em pacientes pós alta hospitalar por Covid-19 e a sua correlação com biomarcadores hematológicos, hormonais e inflamatórios - Beltrão, Daniele Carvalhal de Almeida (2022)
Introduction: Endocrine, metabolic, and hematological factors influence the prognosis of coronavirus disease 2019 (COVID-19). Additionally, COVID-19 may worsen or cause impaired cognition and depressive symptoms. We aim to analyze the impact of biological parameters on neuropsychological changes in patients with moderate to severe SARS-CoV-2 infection after hospital discharge. Methods: In this prospective cohort study, between June and August 2020, we collected laboratory data (thyroid function, vitamin D, inflammatory biomarkers, and hematological features) from 273 hospitalized COVID-19 patients. After hospital discharge (30 – 45 days), 74 patients (filtered by eligibility criteria) were followed up for two months. We split them into preserved cognition (47) and cognitive impairment (27) groups based on a Mini-Mental State Examination (MMSE) score of >23 or ≤23 (respectively). We also split into depressed (28) and nondepressed (46), based on a Beck Depression Inventory (BDI-13) score of >9 or ≤9 (respectively). We performed data analysis to identify biomarkers that affect neuropsychological outcomes. Results: 74 patients [male 66.2%; mean age: 56 (45–68) years] were stratified. The mean hospital length stay was 6 (4- 8) days. We found features that predicted post-COVID-19 cognitive impairment using the ROC curve (AUC score): age (0.82), hemoglobin (0.70), RDW (0.69), LDH (0.69), IL-6 serum (0.68), vitamin D (0.63) and TSH (0.63). We also found ROC curve (AUC score) predictors for depression outcome: D-dimer (0.70), hemoglobin (0.66), age (0.65), RDW (0 .62) and vitamin D (0.61). In multivariate logistic regression (corrected for comorbidities), biomarkers were independent risk factors for cognitive impairment after COVID-19: TSH > 3.63 μIU/mL (OR 14.9 CI 2.06-309, p=0.02); age > 60 years (OR 9.06 CI 2.7–35, p=0.0006); hemoglobin < 13 g/dL (OR 4.46 CI 1.59-13, p=0.003); IL-6 > 68 pg/ml (OR 4.24 CI 1.45-13, p=0.009); Muscle area (MA) < 101 cm² (OR 3.65 CI 1.21-11.7, p=0.024); and 25-OH vitamin D < 21.3 (OR 3.61 CI 1.26-11, p=0.019). We performed the same analysis for post-COVID- 19 depression and found: age > 56 years (OR 5.63 CI 1.69 – 21, p=0.007); D-dimer > 730 ng/ml (OR 5.52 CI 1.93-17, p=0.002); hemoglobin < 13.4 g/dL (OR 3.86 CI 1.38-11.6, p=0.011); RDW > 13.6% (OR 3.57 CI 1.27-10.8, p=0.018); 25-OH vitamin D < 25 (OR 3.11 CI 1.16-8.7, p=0.026). Conclusion: Hospital admission biomarkers, TSH, hemoglobin, Ddimer, RDW, IL-6, and serum vitamin D levels may predict cognitive impairment and depression in COVID-19 patients after discharge.